Preparation and Quality Evaluation of Thekua Incorporated with Germinated Finger Millet (Ragi) Flour - Dangal, Anish; Dhakal, Anish; Shah, Rajesh; Timsina, Diksha; Dahal, Sangam (Journal of Food Technology Research, 2021)
The main aim of this study was to prepare thekua with the incorporation of germinated finger millet also known as ragi, flour and to perform its sensory as well as physicochemical analysis. The wheat flour and finger millet (ragi) flour were mixed with variation at the proportion of 87.5:12.5, 81.25:18.75, 100:0, 75:25 and 93.75:6.25 labeled as samples A, B, C, D and E respectively., while semolina (20 g), sugar (30 g), oil (20 g) and water (20 g) were kept constant for every formulation. The FFA and acid value of the oil used was found to be 0.110±0.02 and 0.221±0.03 respectively. The moisture content of sugar used was found to be 0.16±0.01. Sample ‘E’ was considered best as per the acceptability by panelists and had crude fiber (%), calcium content (mg/100g), tannin (mg/100g), phytate (mg/100g), carbohydrate and total energy (Kcal/100g) of 0.24±0.01, 18.6±0.02, 27.03±0.86, 135.97±1.15, 64.42±0.04 and 512.41±0.07 respectively. Increase in fiber content and minerals was seen in best sample product with the incorporation of germinated finger millet (ragi) flour.